Boosting the quaternary ammonium halides catalyzed CO2 coupling with epoxides on the hollow mesoporous silica sphere. (July 2022) - Razaghi, Masoumeh; Khorasani, Mojtaba
Abstract: Although many efforts have been devoted to the development of novel catalytic protocols on the direct coupling of carbon dioxide with the epoxides, introducing simple, low cost and efficient catalysts, while can be operated under mild reaction conditions, remained with challenges. Herein, we wish to disclose the hollow sphere mesoporous silica (HMS) sphere concomitant with tetraethylammonium bromide (TEAB) can efficiently convert CO2 and various types of epoxide to the corresponding 5-ring carbonates under 10 bar CO2 at 70 °C within a short reaction time. The monodisperse HMS with oriented mesochannels was prepared through a simple hard-templating approache. Some commercially available quaternary ammonium salts such as tetrabutylammonium bromide, tetrabutylammonium iodide and tetrabutylammonium chloride as well as suitable reference catalysts for example sSiO2 hard template, sSiO2 @mSiO2 without hollow region, mesoporous silica nanoparticle (MSN) and SBA-15 were also evaluated under optimized reaction conditions to gain more detail about the accurate role of quaternary ammonium halide and HMS structure in the catalyst activity. The results demonstrated that the presence of a hollow region in the interior of the catalyst increases the local concentration and retention time of CO2 in the catalyst pores where tetraethyl ammonium bromides through a confinement effect can lead to high conversion of CO2 molecules. The catalyst was easily recovered and reused in 6 successive reaction runs during coupling styrene oxide and CO2 with only a slight decrease of reactivity. Graphical Abstract: ga1 Highlights: A Hollow mesoporous silica-tetraethyl ammonium system was found to be a simple catalyst for the CO2 fixation. Hollow spheres lead to enhancement of gas molecule availability. The short channel could improve mass transfer. The small size of catalyst pore shows the confinement effect for tetraethylammonium bromide. Various selected reference catalysts were examined to prove the role of each part of catalytic systems.